Analisis Kelayakan Usaha Chicken Rice Bowl pada Perusahaan XYZ - Aulia, Muhammad Faris; Baldan, Raditya Seivel; Ardiningrun, Aisha Kurnia; Aisyah, Alya; Himawan, Dennis; Sebayang, Veralianita Br; Munawwaroh, Thoifatul (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the financial and non-financial feasibility of the "XYZ: Chicken Rice Bowl" ready-to-eat food business operating in a campus environment. A mixed-methods approach (combining qualitative and quantitative methods) was employed, with data collected through interviews, observations, and a literature review. The non-financial analysis covered management, legal, socio-cultural, environmental, and technical aspects, while the financial analysis utilized investment indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit-Cost Ratio (Net B/C), Gross Benefit-Cost Ratio (Gross B/C), and Payback Period. Additionally, a sensitivity analysis using the switching value method was conducted to assess the business’s resilience to changes in key variables. The results indicate that the XYZ business is feasible, with an NPV of IDR 109,470,969, an IRR of 47%, a Net B/C of 3.78, a Gross B/C of 1.07, and a payback period of 3 years and 4 months. However, the business is sensitive to a 7.68% decrease in production volume and a 19.44% increase in raw material prices. Therefore, cost management strategies and sales enhancement measures are required to ensure the business’s sustainability.